2020
DOI: 10.1038/s41598-020-71336-9
|View full text |Cite|
|
Sign up to set email alerts
|

NT5C2 methylation regulatory interplay between DNMT1 and insulin receptor in type 2 diabetes

Abstract: Epigenetics alternation of non-genetic variation and genome-wide association study proven allelic variants may associate with insulin secretion in type 2 diabetes (T2D) development. We analyzed promoter DNA methylation array to evaluate the associated with increased susceptibility to T2D (30 cases, 10 controls) and found 1,091 gene hypermethylated in promoter regions. We performed the association study of T2D and found 698 single nucleotide polymorphisms in exon and promoter sites by using 2,270 subjects (560 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Vast evidence suggests that DNMT1 can regulate cell cycle and tumor suppressor gene expression, which is crucial in tumor metastasis and linked to poor prognosis [ 23 , 24 ]. Besides, studies have confirmed that DNMT1 is associated with other common diseases, such as type II diabetes [ 25 ], Alzheimer's disease [ 26 ], and periodontal disease [ 27 ]. Recent research also revealed that DNMT1 can mediate the polarization of M1 alveolar macrophages in ALI [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vast evidence suggests that DNMT1 can regulate cell cycle and tumor suppressor gene expression, which is crucial in tumor metastasis and linked to poor prognosis [ 23 , 24 ]. Besides, studies have confirmed that DNMT1 is associated with other common diseases, such as type II diabetes [ 25 ], Alzheimer's disease [ 26 ], and periodontal disease [ 27 ]. Recent research also revealed that DNMT1 can mediate the polarization of M1 alveolar macrophages in ALI [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of DNA methylation in the genome is achieved by DNA methyltransferases such as DNMT1, DNMT3A, and DNMT3B [ 229 , 230 , 231 ]. DNMT1 affects IR gene expression through the transfection of 5′-nucleotidase, cytosolic II (NT5C2), an enzyme that dephosphorylates noncyclic nucleoside monophosphates into nucleoside and inorganic phosphate [ 232 , 233 ] ( Figure 5 ). DNMT1 epigenetically regulates NT5C2 and the IR.…”
Section: Molecular Mechanisms Of Modulators Targeting the Irmentioning
confidence: 99%
“…DNMT1 epigenetically regulates NT5C2 and the IR. Overexpression of DNMT1 stimulated DNA hypermethylation of NT5C2, leading to the silencing of the NT5C2 gene and the inhibition of IR gene expression [ 32 , 232 ]. Knockdown of NT5C2 induced the overexpression of DNMT1 and inhibition of the IR [ 232 ].…”
Section: Molecular Mechanisms Of Modulators Targeting the Irmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, T2D is the most common type of diabetes, accounting for 90–95% of all diabetes cases, and is primarily characterized by pancreatic beta-cell dysfunction and insulin resistance ( 2 ). T2D can lead to serious clinical complications such as diabetic cardiomyopathy, retinopathy, nephropathy, and neuropathy, with high rates of disability and mortality ( 3 ). As lifestyle habits have changed, the number of T2D patients globally has increased significantly.…”
Section: Introductionmentioning
confidence: 99%